GRAMMAR TRANSLATION METHOD: EXPLORING ADVANTAGES AND DISAVANTAGES - Mamadjanova, Maftuna Uktamovna; Xomidova , Madinabonu Sultonboy qizi (Educational Research in Universal Sciences, 2023)
The Grammar Translation Method (GTM) has been a widely used approach to language teaching for many years. This article aims to explore the advantages and disadvantages of GTM in the context of English as a Foreign Language (EFL) classes. By examining the historical background, key principles, and practical implications of GTM, this article provides a comprehensive analysis of its effectiveness in language instruction.